Asylum for sale : profit and protest in the migration industry - McGuirk, Siobhán; Pine, Adrienne (PM Press, 2020)
"This explosive new volume brings together a lively cast of academics, activists, journalists, artists, and people directly impacted by asylum regimes to explain how current practices of asylum align with the neoliberal moment, and to present their transformative visions for alternative systems and processes. Through essays, artworks, photographs, infographics, and illustrations, Asylum for Sale: Profit and Protest in the Migration Industry regards the global asylum regime as an industry characterized by profit-making activity: brokers who demand extortionate fees to facilitate border crossings; contractors and firms that erect walls, fences, and watchtowers while lobbying governments for bigger "security" budgets; corporations running private detention centers and "managing" deportations; private lawyers charging exorbitant fees; "expert" witnesses building their reputations in courthouses; and NGO staff establishing careers while placing asylum seekers into new regimes of monitored vulnerability. Asylum for Sale offers a fresh and wholly original perspective by challenging readers to move beyond questions of legal, moral, and humanitarian obligations that dominate popular debates regarding asylum seekers. Digging deeper, the authors focus on processes and actors often overlooked in mainstream analyses and on the trends increasingly rendering asylum available only to people with financial and cultural capital. The reader is invited to carefully probe every aspect of the asylum process from crossings to aftermaths. Exhaustive in scope, the book covers a sweeping range of national contexts providing an in-depth exploration of complex, international networks, policies, and norms that impact and implicate people seeking asylum around the world. In highlighting protest as well as profit, Asylum for Sale strikes a crucial balance of critical analyses and proposed solutions for resisting and reshaping current and emerging immigration norms"--